Dynamics of Bureaucratic Neutrality Policy in Indonesia - Dwiyanto Indiahono (Puslatbang KDOD Lembaga Administrasi Negara, 2022)
This research reveals the dynamics of relations between civil servants and political parties in Indonesia from the Old Order, the New Order to the Reform Era. This study is an important effort to observe the dynamics of civil servants and political parties in Indonesia and create social learning contributions for the betterment of the country. A qualitative research method with secondary data/literature study was selected. The literature study examined policy documents related to bureaucratic neutrality in the Old Order, New Order, and Reform Era. The study data were collected through documentation, including data from papers related to bureaucratic neutrality in the periods above. The study shows that the idea of bureaucratic neutrality had been initiated since the Old Order, disappeared during the New Order, and was reborn in the Reform Era. The challenge of bureaucratic neutrality was the pull of political parties in the parliamentary system during the Old Order, the power of bureaucracy to be the political supporters of the rulers during the New Order, and the contestation of presidential and regional head elections in the Reform Era, which often tests bureaucratic neutrality